2022
DOI: 10.1021/acs.jpcc.2c02611
|View full text |Cite
|
Sign up to set email alerts
|

Water Oxidation in the Presence of a Nickel Coordination Compound: Decomposition Products, Fe Impurity in the Electrolyte, and a Candidate as a Catalyst

Abstract: Sustainable energy sources require a large-scale storage system. Water electrolysis toward hydrogen formation is a remarkable method for energy storage. However, oxygen-evolution reaction (OER) through water-oxidation reaction is a bottleneck in water-splitting systems. Different Ni-based molecular structures have been claimed to be OER catalysts. However, the impact of Ni (hydr)­oxides formed by the degradation of Ni-based molecular structures on OER is a challenging issue. The effect of electrolyte impurity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…As shown in Figure a, the LSV between 1.3 and 1.5 V belongs to the oxidation of the Ni foam; it shows the LSV curves with 85% iR compensation of N,F–FeO­(OH)–CO 3 –NF and its comparative sample. Among them, N,F–FeO­(OH)–CO 3 –NF has excellent OER activity with the overpotential of 248 mV at 10 mA·cm –2 , which is higher than that of the catalysts IrO 2 –NF (341 mV), N–FeO­(OH)–CO 3 –NF (260 mV), and N,F–FeO­(OH)–NF (311 mV), especially under a relatively higher current density.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure a, the LSV between 1.3 and 1.5 V belongs to the oxidation of the Ni foam; it shows the LSV curves with 85% iR compensation of N,F–FeO­(OH)–CO 3 –NF and its comparative sample. Among them, N,F–FeO­(OH)–CO 3 –NF has excellent OER activity with the overpotential of 248 mV at 10 mA·cm –2 , which is higher than that of the catalysts IrO 2 –NF (341 mV), N–FeO­(OH)–CO 3 –NF (260 mV), and N,F–FeO­(OH)–NF (311 mV), especially under a relatively higher current density.…”
Section: Resultsmentioning
confidence: 99%
“…4. In addition to alkaline conditions, 26 γ-NiO(OH) is a candidate for OER catalysis in the presence of compound 1 at pHs 7.0 and 3.0 (Scheme 2). 5.…”
Section: Acs Applied Energy Materialsmentioning
confidence: 99%
“…25 It was recently demonstrated that during OER and at very low overpotentials, a tetranuclear Ni complex is decomposed to Ni (hydr)oxide. 26 Oxidation of Ni ions could trigger this decomposition reaction even at the first CV. 26 In the presence of Fe impurity in KOH or devices, Ni (hydr)oxide forms an efficient catalyst for OER.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations